The dressmaker of Khair Khana : five sisters, one remarkable family, and the woman who risked everything to keep them safe - Tzemach Lemmon, Gayle (New York, NY : Harper, 2011)
The incredible true account of Kamila Sidiqi who, when her father and brother were forced to flee Kabul, became the sole breadwinner for her five siblings. Armed only with grit and determination, she picked up a needle and thread and created a thriving business of her own and held her family together.
The news arrives and everything changes -- A time of goodbyes -- Stitching the future back together -- The plan goes to market -- An idea is born...but will it work? -- Class is in session -- An unexpected wedding party -- A new opportunity knocks -- Danger in the night sky -- Kabul Jan, Kaweyan, and Kamila's faith in good fortune.
Includes bibliographical references (p. 245-256).
Keywords: Sediqi, Kamela, -- 1977-; Sediqi, Kamela, -- 1977- -- Family; Dressmakers -- Afghanistan -- Kabul -- Biography; Sisters -- Afghanistan -- Kabul -- Biography; Businesswomen -- Afghanistan -- Kabul -- Biography; Community life -- Afghanistan -- Kabul -- History -- 21st century; Khair Khana (Kabul, Afghanistan) -- Biography; Kabul (Afghanistan) -- Biography; Kabul (Afghanistan) -- Social life and customs -- 21st century; Kabul (Afghanistan) -- Economic conditions -- 21st century